2011
DOI: 10.1007/s12072-011-9262-2
|View full text |Cite
|
Sign up to set email alerts
|

Serum retinol binding protein 4 and clinical outcome in postoperative biliary atresia

Abstract: Serum RBP4 levels decreased in BA patients compared with normal participants, and its levels declined significantly in patients with more severe disease. RBP4 may play a role in the pathogenesis of hepatic fibrosis and serve as a possible biomarker reflecting disease severity in postoperative BA patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…RBP, mainly synthesized and stored in hepatocytes, is a specific carrier of retinol, transporting it from the liver to various target tissues. Decreased RBP4 plays a possible role in the pathogenesis of hepatic fibrosis and serves as a potential biomarker reflecting disease severity in postoperative biliary atresia patients 23) . Additionally, both animal and human studies have shown that RBP4 might be involved in the development of insulin resis- tance and diabetes 24,25) .…”
Section: Discussionmentioning
confidence: 99%
“…RBP, mainly synthesized and stored in hepatocytes, is a specific carrier of retinol, transporting it from the liver to various target tissues. Decreased RBP4 plays a possible role in the pathogenesis of hepatic fibrosis and serves as a potential biomarker reflecting disease severity in postoperative biliary atresia patients 23) . Additionally, both animal and human studies have shown that RBP4 might be involved in the development of insulin resis- tance and diabetes 24,25) .…”
Section: Discussionmentioning
confidence: 99%
“…Researches have found that the concentration of serum RBP4 is negatively correlated with the disease severity in patients with early HCV liver fibrosis, and its concentration decreases as the degree of liver fibrosis increases [12]. The negative correlation between RBP4 and the severity of liver fibrosis might be due to the decreased level of RBP4, which participated in the activation of hepatic stellate cell overexpression and the deposition of type I collagen in the liver, that promoted the progression of liver fibrosis [12,23], which eventually developed into liver cirrhosis or HCC. In summary, changing the concentration of serum RBP4 might represent a sensitive indicator of liver function injury.…”
Section: Discussionmentioning
confidence: 99%